Respuesta :
The solution would be like this for this specific problem:
ab/a+b = c
b = -1 + a
for c:
(5(-1 + 5))/(5 + (-1 +5))
5(4)/ 5 + 4
20 / 9
The correct answer between all the choices given is the first choice or letter A. I am hoping that this answer has satisfied your query and it will be able to help you in your endeavor, and if you would like, feel free to ask another question.
Answer:
Option A
Step-by-step explanation:
The given literal equation is [tex]\frac{ab}{a+b}=c[/tex]
with b = ( a-1 )
We have to calculate the value of c when a = 5
Now we put b = ( a - 1 ) in literal equation
[tex]\frac{a(a-1)}{a+(a-1)}=c[/tex]
[tex]c=[\frac{a(a-1)}{2a-1}][/tex]
Now we have to calculate the value of c when a = 5
[tex]c=\frac{5(5-1)}{(2*5)-1}[/tex]
[tex]\frac{5\times 4}{10-1}[/tex]
[tex]=\frac{20}{9}[/tex]
Option A is the answer.